The New First-in-Human EMA Guideline: Disruptive or Constructive? Outcomes From the First EUFEMED Discussion Forum - Breithaupt-Grögler, Kerstin; Hardman, Tim; de Hoon, Jan; Donazzolo, Yves; Rottey, Sylvie; Sourgens, Hildegard; Stringer, Steffan (Frontiers in Pharmacology, 2019)
The EUropean Federation for Exploratory MEdicines Development (EUFEMED) organised a meeting in Leuven, Belgium entitled ‘The new FIH EMA guideline: Disruptive or constructive?’ to provide a forum for stakeholders to discuss the guideline’s operational impact. The revised EMA Guideline on strategies to identify and mitigate risks for first-in-human (FIH) and early clinical trials with investigational products was published on 20 July 2017. The revision gave guidance on sentinel dosing/staggering of subjects within a multiple-ascending dose (MAD) clinical trial, permissible maximum exposure/investigation of supra-therapeutic doses and dose escalations above the no-observed adverse effect level. As the guidelines came into operation on 1 February, 2018 it was assumed that by the date of the meeting many early-phase stakeholders had gathered sufficient first-hand experience of working within the guideline to discuss their thoughts on its impact. The concluding part of the meeting focused on the possible differences between European countries in handling the revised FIH guideline and ways of achieving harmonisation. Information on current industry practice was gathered by online polling during the meeting, where perception of the revised guideline as either ‘disruptive’ or ‘constructive’ was explored at the start and at the end of the Forum along with recommendations on reducing future regulatory discordance. It was generally agreed that the necessary changes encompassed by new guidelines included both constructive and disruptive aspects. The final vote on whether the new FIH guideline is disruptive or constructive was taken by 69 delegates: 51% stated that it was both constructive and disruptive, 48% decided on constructive, none on disruptive and 1% were still undecided. It was generally accepted that stakeholders need to continue in a process of stakeholder engagement and discussion, particularly on critical safety issues. Such an approach allows partners to adopt a proactive approach to sharing best practice. For example, attendees agreed that a ‘Question and Answer’ document harmonised between the European agencies is required for the sentinel approach and for the selection of supratherapeutic doses.